Cultural suitability of schema therapy: a qualitative exploration of clinician views - Irene R. Martin; Sandra E. Stewart; Phillip Tchernegovski; Bethany D. Devenish (Australian Journal of Psychology)
Objective There is a growing popularity in the worldwide use of schema therapy (ST) to address a variety of psychological disorders. Yet, research into the cultural suitability of ST is scarce. This study aimed to explore ST clinicians’ experiences of the cultural suitability of ST.Method Eleven clinicians from nine countries were interviewed about their experiences of practising ST. Interviews were analysed using reflexive thematic analysis.Results Two main themes, each with subthemes, were identified. The first theme was considerations for Cultural Context and Content: (i) Incongruence with Cultural Norms of Emotional Expression, (ii) “Maladaptive” or “Adaptive”, But in What Context?, and (iii) Issues Related to Familism when Addressing Parent/Critic Modes. The second theme focused on clinicians’ Cultural Competence: (i) Perceptions of Reduced Confidence and Competence in Providing Culturally Responsive Practice, and (ii) Clinicians’ Cultural Values Impacting ST Delivery. Participants discussed strategies to improve the cultural-responsiveness of ST, suggesting areas for further development.Conclusion Present findings suggest that ST is not a one-size-fits-all approach, underscoring the need to improve the cultural responsiveness of ST, while better supporting clinicians to develop their cultural competence. Future research is needed to establish evidence-based cultural adaptations for ST.